COMMUNITY RESILIENCE AFFECTED BY THE ERUPTION OF MOUNT SEMERU IN THE ERA OF THE COVID-19 PANDEMIC - Primasari Mahardika Rahmawati; Suhari Suhari; Anggia Astuti; Musviro Musviro (UPT Penerbitan Universitas Jember, 2022)
Introduction: This study is to determine the resilience of the community affected by the eruption of Mount Semeru. The ability of the community to overcome and adapt to severe events in the face of adversity or trauma experienced in life, each community group, has different skills and capacities in responding to the disasters they face. Several variables support the level of community resilience to disasters, namely, social, economic, infrastructure, institutional, and community aspects. Resilience is often interpreted as